2017
DOI: 10.1002/ppap.201700085
|View full text |Cite
|
Sign up to set email alerts
|

Translation of plasma technology from the lab to the food industry

Abstract: The potential of cold plasma as a food processing aid has been demonstrated for a range of processes and products. The potential applications of plasma technology are extensive and include: microbial decontamination, pest control, toxin elimination, food and package functionalisation and many others. However, studies reported to date have principally been at laboratory scale. This paper discusses the status and challenges of transferring the technology to the industry. The major challenges discussed for adopti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
92
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(94 citation statements)
references
References 52 publications
0
92
0
2
Order By: Relevance
“…Furthermore, DBD plasma is very suitable for in‐package inactivation of fresh produce; the reactive oxygen species (ROS) and reactive nitrogen species (RNS) can be generated directly inside sealed packages (Misra, Keener, Bourke, Mosnier, & Cullen, ), which eliminates the risk of postprocess contamination, whereas for the inducer gases, argon and helium as well as nitrogen are the common carrier gases, which were employed for surface modification. However, studies show that inducer gases with the addition of oxygen can improve plasma efficiency of food disinfection (Cullen et al., ). In addition, air and modified packaging gas are also adopted as common plasma gas sources.…”
Section: Fundamentals Of Nonthermal or Cold Plasmamentioning
confidence: 99%
“…Furthermore, DBD plasma is very suitable for in‐package inactivation of fresh produce; the reactive oxygen species (ROS) and reactive nitrogen species (RNS) can be generated directly inside sealed packages (Misra, Keener, Bourke, Mosnier, & Cullen, ), which eliminates the risk of postprocess contamination, whereas for the inducer gases, argon and helium as well as nitrogen are the common carrier gases, which were employed for surface modification. However, studies show that inducer gases with the addition of oxygen can improve plasma efficiency of food disinfection (Cullen et al., ). In addition, air and modified packaging gas are also adopted as common plasma gas sources.…”
Section: Fundamentals Of Nonthermal or Cold Plasmamentioning
confidence: 99%
“…Significantly, the key species and chemical pathways should be easier to measure, control, and reproduce for industry, as only metastables will be presented in PAW treatment (no electric filed, UV, etc.) . Long‐lived reactive oxygen species (ROS) and reactive nitrogen species (RNS) generated in PAW, like hydrogen peroxide (H 2 O 2 ), nitrate (NnormalO3) and nitrite (NnormalO2), should be responsible for physiological roles in biology.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, interest in NTP has gradually transformed from basic research into practical use. Among others, several recent and current review papers have been devoted to food industry or to medical applications . NTP sources have been reviewed, and it has been shown that the mechanisms of NTP's interaction with living cells and tissues are mediated mainly by reactive oxygen and nitrogen species (see or for a review).…”
Section: Introductionmentioning
confidence: 99%